2020
DOI: 10.3390/molecules25030677
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and In Vitro Photocytotoxicity of 9-/13-Lipophilic Substituted Berberine Derivatives as Potential Anticancer Agents

Abstract: The objective of this study was to synthesize the 9-/13-position substituted berberine derivatives and evaluate their cytotoxic and photocytotoxic effects against three human cancer cell lines. Among all the synthesized compounds, 9-O-dodecyl- (5e), 13-dodecyl- (6e), and 13-O-dodecyl-berberine (7e) exhibited stronger growth inhibition against three human cancer cell lines, (HepG2, HT-29 and BFTC905), in comparison with structurally related berberine (1). These three compounds also showed the photocytotoxicity … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 37 publications
2
20
0
Order By: Relevance
“…Our previous report demonstrated the absorption and emission spectra of 9- O -dodecylberberrubine bromide (B7) are 420 nm and 529 nm in the cells [ 6 ]. In the present study, we confirm this phenomenon for B6 and B7 in A549 and H1435 cells after incubation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous report demonstrated the absorption and emission spectra of 9- O -dodecylberberrubine bromide (B7) are 420 nm and 529 nm in the cells [ 6 ]. In the present study, we confirm this phenomenon for B6 and B7 in A549 and H1435 cells after incubation.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, berberine has been demonstrated to be a safety agent for cancer therapy [ 10 ]. In our previous study, we generated a series of compounds from berberine with 9-position-substituted derivatives B2 to B7, which exert better anti-cancer behavior than berberine in human hepatoma, colon and bladder cancer cells [ 6 ]. Here, we demonstrated that berberine derivatives, including 9- O -hexylberberrubine bromide (B4), 9- O -octylberberrubine bromide (B5), 9- O -decylberberrubine bromide (B6), and 9- O -dodecylberberrubine bromide (B7), have better anti-NSCLC activity than berberine (B1) ( Figure 2 and Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations